Focalization in Hans Christian Anderson’s Selected Fairy Tales - Kheirbek, Dr. Taymaa Hussein Kheirbek (Sulaimani Journal for Humanities, 2025)
The fairy tales written by the nineteenth-century Danish author, Hans Christian Andersen, is considered an important part of children’s literature heritage. Studying the narrative tools in H. C. Andersen's tales is extremely significant since they are employed with different aims and for different reasons. This paper reviews the definition of the term ‘Focalization’ and studies its different approaches. Focalization is also analysed as a narrative device in three of H. C. Andersen’s fairy tales: ‘The Red Shoes’, ‘The Girl Who Trod on The Loaf’, and ‘Anne Lisbeth’. Various types of focalization are studied in order to illustrate their roles in the narratives and show how they influence the general meaning. The aim is not to find new interpretations of the stories in question but to show H. C. Andersen's use of various instruments and how their narrative effects are differentiated.
Keywords: Narratology Focalization Hans Christian Anderson Fairy tales